MNE subsidiary evolution from sales to innovation: Looking inside the black box. Issue 1 (February 2017) - Lim, Chaisung; Hemmert, Martin; Kim, Seunghoi
Highlights: We study the role change of a MNE sales subsidiary to innovation. We combine the subsidiary evolution and user innovation perspectives. We conduct a case study of a semiconductor MNE subsidiary in South Korea. Subsidiary-, market- and event-related factors enable the role change. We suggest directions for theory extensions of MNE subsidiary evolution. Abstract: Whereas the innovation-related evolution of multinational enterprise (MNE) subsidiaries has been extensively studied, the numerous sales subsidiaries in MNE networks have received little attention in this context. This study examines the evolution process of a sales subsidiary towards acquiring innovation-related capabilities and actively supporting innovation activities of a MNE. The evolution is explained in terms of technical information flow in an in-depth case study of a semiconductor MNEs' sales subsidiary in South Korea. We find that the evolution of the sales subsidiary to innovation support has been enabled by a combination of subsidiary-related, lead market-related and event-related factors. We contribute to the literature on MNE subsidiary evolution by studying the unexplored evolution of a sales subsidiary. We combine the general framework of subsidiary evolution with the lead user perspective and suggest directions for potential theory extensions on MNE subsidiary evolution.